CSR Communication and Organizational Identification: Exploring the relationship between communicating corporate social responsibility and organizational members’ identification - Riikonen, Iina-Riikka (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Even though corporate social responsibility (CSR) and communications about it have received a substantial deal of academic attention in recent years, organizations’ internal stakeholders have been neglected as an audience. Internal audiences are known to be one of the keenest followers of corporate communications, and hence, they can be argued to follow and evaluate their employers’ CSR communications as well. Through auto-communication, or the internal reception of external communications, messages cease to merely add information but gain a symbolic element to them. This ensemble is argued to effect, among others, the organizational identification of organizational members. The extended model of organizational identification comprehends positive (traditional), ambivalent, neutral and disidentification. The aim of this thesis is to shed light on the relationship between organizational identification and organizational members’ perceptions of their employers’ external CSR communications. A quantitative approach was chosen to serve the objectives of the present thesis and as the method for conducting empirical research. The sample was collected using exponential non-discriminative snowball sampling via an online survey. The data were analyzed using multinomial logistic regression as well as hierarchical and stepwise multiple regression. The results reveal some connections between CSR communications and organizational identification, but the theoretical model adopted did not gain empirical support as a whole. The key finding of the thesis is that members’ perceptions of the organizational identity in relation to CSR and their personal need for identification were predictors of both the level of positive identification as well as the classification of respondents into groups based on the type of identification. The depth of the exchange relationship between the respondent and the organization was a predictor of the levels of positive and/or neutral identification. A positive construed external image and a positive assessment of the sufficiency of CSR communications were also positively related to the level of organizational identification. Only a negative construed external image was related to ambivalent identification. Even though a straightforward relationship with communications was not established, the data gives hint of an underlying and indirect role in the identification process. All in all, the theoretical framework adopted was assessed to be blown out of proportion in relation to the actual relevance in the real world.

Vaikka yritysvastuu ja siihen liittyvä viestintä ovat viime vuosina olleet suuresti akateemisen huomion kohteena, ovat organisaation jäsenet jääneet toistaiseksi vähälle huomiolle vastuullisuusviestinnän vastaanottajina. Yritysten sisäisten audienssien tiedetään olevan yksi aktiivisimmista ulkoisen viestinnän seuraajaryhmistä, joten heidän voidaan myös olettaa seuraavan ja arvioivan työnantajiensa vastuullisuusviestintää. Autokommunikaation eli ulkoisen viestinnän sisäisen vastaanottamisen myötä viestit saavat tiedollisen ulottuvuuden lisäksi symbolisen merkityksen. Tämän viestikokonaisuuden arvioidaan vaikuttavan muun muassa organisaatioiden jäsenten identifioitumiseen työnantajaansa. Identifikaatiota on positiivista (perinteistä), ristiriitaista, neutraalia ja etääntymistä. Tämän tutkielman tarkoituksena on siten tutkia yritysten sisäisten sidosryhmien kokemaa organisatorisen identifikaation suhdetta ulkoiseen vastuullisuusviestintään. Tutkimusongelmaa on lähestytty empiriassa kvantitatiivisin menetelmin: multinominen logistinen regressio ja hierarkkinen sekä askeltava monimuuttujaregressioanalyysi. Aineisto kerättiin kyselylomakkeen avulla lumipallo-otannalla. Tulokset paljastavat joitain yhteyksiä vastuullisuusviestinnän ja koetun identifikaation välillä, mutta teoreettinen malli kokonaisuudessaan ei saanut aineiston pohjalta empiiristä tukea. Tutkielman päälöydös on että organisaation jäsenten käsitys yrityksen identiteetistä suhteessa yritysvastuuseen ja henkilökohtainen tarve samaistua ovat ennustajina sekä positiivisen identifikaation tasoa arvioitaessa että luokiteltaessa vastaajia ryhmiin identifikaatiotyylin perusteella. Henkilön ja yrityksen välisen vaihdantasuhteen syvyys ennusti positiivista ja/tai neutraalia identifikaation tasoa. Vastaajan positiivinen näkemys yrityksen maineesta yritysvastuun saralla sekä positiivinen arvioi vastuullisuusviestinnän riittävyydestä olivat myös yhteydessä positiivisen identifikaation tasoon. Vain yrityksen negatiiviseksi koettu maine vastuullisuuden saralla oli yhteydessä ristiriitaiseen identifioitumiseen. Vaikka suoraa yhteyttä viestintään ei pystytty todistamaan, antaa aineisto viitteitä viestinnän välillisestä roolista identifioitumisprosessissa. Kokonaisuudessaan teoreettisen viitekehyksen arvioitiin olevan ylikorostunut suhteessa asiakokonaisuuden todelliseen merkitykseen reaalimaailmassa.